A mixed-methods study exploring adherence to the referral of severely sick children in primary health care in Southern Ethiopia - Habtamu Beyene; Dejene Hailu; Henok Tadele; Lars Åke Persson; Della Berhanu (BMC, 2021)
Abstract Background We have shown that Ethiopian primary healthcare providers refer only half of the severely sick children who, according to guidelines, should get an urgent referral. Frequently parents of referred ill children don't bring their children to the next level. We aimed to describe the referral of severely ill Ethiopian children based on primary healthcare register reviews and explore health care providers' and parents' perceptions regarding factors that hinder or enhance referral. Methods A mixed-methods study was conducted in 11 districts and a town administration of the Hadiya zone in Ethiopia's Southern region from May to June 2019. Data collection included interviews and focus group discussions with healthcare providers, key informant interviews with parents of sick children who had been referred, and reviewing registers of sick children treated during the last 12 months at health posts and health centres. We analysed the association between healthcare providers' and sick children's characteristics and providers' compliance with referral guidelines for sick children 0-59 months old. Content analysis was undertaken to explore the perceived factors that influenced referral and adherence to referral from providers' and parents' perspectives. Results Healthcare providers did not refer nearly half of the severely ill children that should have been referred, according to guidelines. Providers who had received in-service training on child healthcare were more likely to adhere to referral guidelines. The severity of the child's illness and mobile phone communication and transport availability were perceived to be positively associated with adherence to referral guidelines. Lack of knowledge of treatment guidelines and skills, and high health worker workload, were among the factors perceived to be linked to lower adherence to guidelines. The healthcare providers considered parents of referred sick children as having low compliance with the referral advice. In contrast, parents had the opinion that compliance with a referral for sick children was high. Perceived awareness of severity of the child's illness, ability to afford referral costs, and availability of transport or ambulance services were perceived to motivate parents to take their children to the referral facility. Traditional illness perceptions, lack of confidence in the referral site's medical care, and a long distance were perceived to hurdle caregivers' referral compliance. Conclusions We found that the healthcare providers' adherence to referral guidelines was not optimal. Care providers and parents had divergent opinions on parents' compliance with referral advice. Factors related to the health system, family economy, and available ambulance services influence whether care providers and parents pursued severely ill children's referral. Adequate referral of sick children is an aspect of primary healthcare quality that is essential to avoid unnecessary under-five deaths.